Organoleptic Tests of The Addition of Telang Flower Extract (Clitoria ternatea) on Cow's Milk Yoghurt (Bos taurus) Production in Air Tawar Village, Langkat - Yusraini Baubara; Arini Shinta Zahara; Silvia Wardania (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Yogurt is the oldest dairy product and is quite popular almost all over the world. Yogurt comes from pure cow's milk. Butterfly pea (Clitoria ternatea ) often referred to as butterfly pea or blue bean is a distinctive flower with a single petal in purple, blue, pink and white. Researchers wanted to see the effect of adding butterfly pea flower extract (Clitoria ternatea) to cow's milk yogurt (Bos taurus). This study employs a quantitative approach as its method. A quantitative approach was used to understand what the research subjects experienced from the color, taste, aroma and texture of the yogurt. The results of the study found that the addition of butterfly pea flower extract (Clitoria ternatea) at different levels had an effect on the organoleptic characteristics and texture of yogurt. The best practice produces organoleptic characteristics of taste (slightly sour), color (light blue), texture (slightly thick) and aroma (typical of yogurt).